Constructing the meaning for national human resources development in Malaysia - Devadas, Udaya Mohan; Silong, Abu Daud; Ismail, Ismi Arif; Krauss, Steven Eric (2011)
Malaysia as a successful case for adopting national level human resource development in its national policy planning and implementation can provide new insights to the current knowledge base. In contributing to such new knowledge, this paper, adopting a qualitative research design using grounded theory method, aimed at constructing the meaning for Malaysia’s national level human resource development. It was discovered that Malaysia’s national level HRD has evolved gradually to Human Capital Development (HCD), currently in use, mainly with an economic purpose to resolve its prolonged key challenge of sustaining national unity prioritizing economic progress towards a developed nation.